2012
DOI: 10.1089/apc.2011.0379
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Hemoglobin A1c as Screening for Diabetes Mellitus in HIV-Infected Individuals

Abstract: The American Diabetes Association now recommends hemoglobin A 1c (HbA 1c ) screening for the diagnosis of diabetes. It has been reported that HbA 1c levels underestimate glycemic levels in HIV-infected persons. We examined the performance of HbA 1c as a screening test for diabetes in a group of HIV-infected people without diabetes. We conducted a retrospective cross-sectional cohort study among HIV-infected patients determining the sensitivity and specificity of HbA 1c as a screening test compared to fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 17 publications
(19 reference statements)
4
41
1
Order By: Relevance
“…Although glycation differences have been suggested in HIV-infected compared to -uninfected individuals (2729), in this small subgroup of 80 A5078 study subjects, we did not find evidence that plasma levels of either form of sRAGE studied here were modulated by HIV status. However, we did find progression of CIMT associated with lower baseline esRAGE levels among those with HIV infection, which is consistent with a previous report in HIV-uninfected, diabetic individuals (30).…”
Section: Discussioncontrasting
confidence: 95%
“…Although glycation differences have been suggested in HIV-infected compared to -uninfected individuals (2729), in this small subgroup of 80 A5078 study subjects, we did not find evidence that plasma levels of either form of sRAGE studied here were modulated by HIV status. However, we did find progression of CIMT associated with lower baseline esRAGE levels among those with HIV infection, which is consistent with a previous report in HIV-uninfected, diabetic individuals (30).…”
Section: Discussioncontrasting
confidence: 95%
“…al. (20) compared elevated fasting blood glucose with HgbA1c. Using fasting blood glucose as the gold standard, investigators found that the sensitivity of HgbA1c was poor at 40.9%, but specificity high at 97.5%; peak sensitivity and specificity was found at a HgbA1c cutoff of 5.8%.…”
Section: Diagnosticsmentioning
confidence: 99%
“…The lower HbA1C in the HIV‐infected population was unexpected, as this group had higher rates of anemia, which results in higher HbA1C if caused by iron deficiency anemia . However, this relationship is complex, since the cause of anemia in our cohort was unknown and HbA1C has previously been found to underreport hyperglycemia in HIV‐positive patients . On the other hand, the observation that first visit mean blood glucose (MBG) was also lower in our HIV‐infected group tends to affirm better control in this group.…”
Section: Discussionmentioning
confidence: 57%
“…32 However, this relationship is complex, since the cause of anemia in our cohort was unknown and HbA1C has previously been found to underreport hyperglycemia in HIVpositive patients. 33 On the other hand, the observation that first visit mean blood glucose (MBG) was also lower in our HIV-infected group F I G U R E 1 Neonatal outcomes in metformin monotherapy and glibenclamide-exposed groups vs insulin monotherapy in participants with T2DM and GDM. T2DM, type 2 diabetes; GDM, gestational diabetes; LBW, low birth weight; PNM, perinatal mortality.…”
Section: Discussionmentioning
confidence: 78%